Provoking conditions, management and outcomes of type 2 myocardial infarction and myocardial necrosis. (1st September 2016) - Smilowitz, Nathaniel R.; Weiss, Matthew C.; Mauricio, Rina; Mahajan, Asha M.; Dugan, Kaitlyn E.; Devanabanda, Arvind; Pulgarin, Claudia; Gianos, Eugenia; Shah, Binita; Sedlis, Steven P.; Radford, Martha; Reynolds, Harmony R.
Abstract: Background: Type 2 myocardial infarction (MI) is defined as myocardial necrosis (myonecrosis) due to an imbalance in supply and demand with clinical evidence of ischemia. Some clinical scenarios of supply–demand mismatch predispose to myonecrosis but limit the identification of symptoms and ECG changes referable to ischemia; therefore, the MI definition may not be met. Factors that predispose to type 2 MI and myonecrosis without definite MI, approaches to treatment, and outcomes remain poorly characterized. Methods: Patients admitted to an academic medical center with an ICD-9 diagnosis of secondary myocardial ischemia or non-primary diagnosis of non-ST-elevation MI were retrospectively reviewed. Cases were classified as either MI (n = 255) or myonecrosis without definite MI (n = 220) based on reported symptoms, ischemic ECG changes, and new wall motion abnormalities. Results: Conditions associated with type 2 MI or myonecrosis included non-cardiac surgery (38%), anemia or bleeding requiring transfusion (32%), sepsis (31%), tachyarrhythmia (23%), hypotension (22%), respiratory failure (23%), and severe hypertension (8%). Inpatient mortality was 5%, with no difference between patients with MI and those with myonecrosis (6% vs. 5%, p = 0.41). At discharge, only 43% of patients received aspirin and statin therapy. Conclusions: Type 2 MI and myonecrosis occur frequently in the setting of supply–demand mismatch due to non-cardiac surgery, sepsis, or anemia. Myonecrosis without definite MI is associated with similar in-hospital mortality as type 2 MI; both groups warrant further workup for cardiovascular disease. Antiplatelet and statin prescriptions were infrequent at discharge, reflecting physician uncertainty about the role of secondary prevention in these patients.